Protocols for maintaining a colony of Manduca sexta (tobacco hornworm) suitable for studies of innate immunity and other investigations of a model insect species - Kanost, Michael R.; Gorman, Maureen J.; Rowe, Jennifer; Brummett, Lisa M. (Kansas State University, 2025)
Manduca sexta, the tobacco hornworm, is a lepidopteran species often used as a model organism for biological research. It reaches a large size (~10 g) as a last instar larva, useful for biochemical studies, and its development can be synchronized for studies of endocrinology and developmental regulation. We describe here our detailed protocols for rearing a continuous colony of M. sexta in the laboratory. We feed larvae an artificial diet based on wheat germ and rear larvae at 26°C in individual plastic cups with clean procedures to produce larvae suitable for studies of immune responses. Wandering larvae at the end of larval development are placed in plastic boxes containing vermiculite for pupation, and then pupae are transferred to clean plastic boxes in the incubator. Prior to adult emergence, pupae are placed in a cage with a tobacco plant. Moths mate and oviposit on the leaves, and eggs are collected for continuation of the colony.